Clinicopathologic characteristics and prognostic significance of HER2-low expression in patients with early breast cancer: A systematic review and meta-analysis - Wei, Tong; Wang, Dingyuan; Gao, Songlin; Wang, Xue; Yue, Jian; Kang, Yikun; Ju, Jie; Yang, Zixuan; Shuai, You; Yuan, Peng (Frontiers in Oncology, 2023)
Background: HER2-low expression breast cancer (BC) accounts for approximately 45%-55% of all BC cases. The purpose of this study was to investigate the association of different prognoses between patients with HER2-low expression and HER2-zero BC. Methods: An electronic search of Pubmed, Embase, Cochrane Library, and Web of Science databases were performed to screen studies that included prognostic comparisons between HER2-zero and HER2-low expression groups. A total of 14 retrospective studies involving 52106 patients were included. Results: Our results indicated that HER2-low expression was associated with a significant benefit in OS among all patients with early BC (HR, 0.83; 95% CI, 0.78–0.88), patients with hormone-receptor positive BC (HR, 0.83; 95% CI, 0.77–0.89), and patients with TNBC (HR, 0.78; 95% CI, 0.70–0.87). HER2-low expression was associated with a significant benefit in DFS among all patients (HR, 0.81; 95% CI, 0.71–0.93), patients with hormone receptor-positive BC (HR, 0.81; 95% CI, 0.72–0.90), but no significant difference in DFS was found in patients with TNBC (HR, 0.87; 95% CI, 0.65–1.17). HER2-low expression was associated with a significant benefit in RFS among all patients (HR, 0.90; 95% CI, 0.85–0.95), patients with hormone receptor-positive BC (HR, 0.90; 95% CI, 0.84–0.96), but no significant difference in RFS was found in patients with TNBC (HR, 0.80; 95% CI, 0.55–1.16). Conclusions: Among patients with early-stage BC, patients with HER2-low expression BC had better OS in the overall population, hormone receptor-positive and TNBC subgroups. Besides, favorable DFS and RFS were observed in both the overall population and hormone receptor-positive subgroup.